Functional diversity in reef fish assemblages in the Parque Nacional Sistema Arrecifal Veracruzano, Mexico: Temporal and spatial changes - Russet-Rodríguez, Andy J.; Pérez-España, Horacio; Payán-Alcacio, Juan Á.; Peterson, Mark S.; De La Cruz-Agüero, Gustavo; Enríquez-García, Arturo B.; Ornelas-Vargas, Arelly; Cruz-Escalona, Víctor H. (Frontiers in Marine Science, 2023)
TThe Parque Nacional Sistema Arrecifal Veracruzano (hereafter called PNSAV) is the largest coral reef extension in the central region of the Gulf of Mexico. These reefs are unique since they have developed near a coastal environment that is directly influenced by the discharges of Veracruz city, the rivers located on the continental shelf, and the port of Veracruz. This study evaluates the functional diversity, in terms of richness, evenness, and divergence, of the PNSAV fish community. We were interested in quantifying any similarities or differences in functional diversity metrics when one examines reef fish assemblages on a single reef or joint reef subsystems; thus, is there a difference based on scale? A total of 297 fish assemblages were observed in seven PNSAV reefs between May 2006 and April 2021. Significant differences were found in the Functional Richness of the assemblages between subsystems, years, and reef-depth interaction, but none were found among the reefs, or between seascapes. The Functional Diversity presented annual mean values between 0.83 (sd= 0.085) and 0.90 (sd= 0.068) and did not show statistical differences between years, seascape, or reefs. In contrast, statistical differences were found between subsystems, and depth level and the seascape-depth interaction. The annual mean Functional Evenness values ranged between 0.34 (sd= 0.128) and 0.44 (sd= 0.060), and significant differences were detected between years, reef, and reefs-depth level interaction, but no difference were found between subsystems. Reef-fish diversity was greater within the north coral reef subsystem than the southern of the PNSAV. There were no overall tendencies for increased functional diversity throughout the time during this study.